“I was a full time proper smoker”: A qualitative exploration of smoking in the home after childbirth among women who relapse postpartum - Orton, Sophie; Coleman, Tim; Lewis, Sarah; Cooper, Sue; Jones, Laura L. (Public Library of Science, 2016)
Background: Many women stop smoking during pregnancy but relapse shortly afterwards, potentially putting their infants at risk of secondhand smoke (SHS) exposure. Women who were able to stop during pregnancy may be a motivated group, receptive to making behaviour changes postpartum to protect their infant from SHS exposure. Understanding more about their experiences of relapse, and if this influences home smoking behaviours and children’s exposure to SHS in the home may help to inform intervention development to prevent infant SHS exposure.